Kajian Eksperimental Pengurangan Gas Emisi Co2 dengan Teknologi Biosphere - Dedy Arithama; Khairil Khairil; Iskandar Iskandar (Jurnal Teknik Mesin Unsyiah, 2016)
According of air pollution technology can be reduced by two methods: by using the Oceans method or Biosphere method. Oceans method known  a way that is burying CO2 in the deep of sea water of oceans. Biosphere method is known as the method of using natural and plant, namely by multiplying the trees in the neighborhood that will create air quality in the surrounding environment is increased. With this method made design research tool that room 1 and room 2 with dimensions of 50 cm x 50 cm x 100 cm with isolated condition. In the first room filled with gas emission vehicle for 60 minutes and then measured by a gas analyzer in order to determine the composition of vehicle exhaust emissions. Gas emissions of vehicles streamed into the room space 1and  2 by using a blower  through 3 pieces of flexible hoses. In room 2 vehicle emissions react with activated carbon and tree to absorbs CO2 from vehicle emissions, then for 60 minutes once for 5 hours of data taken and observed. Research results show, with the absorption of CO2 emission and method biosphere technology is very significant influence as evidenced from the graph of CO2 emission and absorption of O2 release to the environment. Variations trees greatly affect the ability of absorption of CO2 gas emissions and O2 release to the environment, also the effect of adding activated carbon additive affects the absorption process of the addition of CO2 emissions and the release of O2 into the environment with a total absorption of 60% CO2 and release O2 at 5.8%. Trees are able to absorb the most CO2 emissions in the period of the most rapid and release O2 is trambesi tree with a total absorption of 80% CO2 and the release of O2 by 7.2% with a time of 300 minutes with the absorption of 3.33 ppm. m2 / min.